(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The main goal of this study is to improve the performance of laser rotating of non-contact human body scanning system, and to get the true and accurate 3D information of measured human body. In the aspect of obtaining the human body pixel coordinates, the extraction accuracy of laser stripe center is one of the important factors to affect the measurement accuracy. Therefore, this paper mainly discussed the algorithm of obtaining and the curve fitting human body scanning laser stripe center pixel coordinates. In the analysis of the characteristics of the human body laser stripe images, put the improved column processing algorithm to compute stripe center position. Using the Bezier curve fitting of the human body scanning light trap center line, effectively improved the smoothness of the human body scanning light trap center line.